Paradigmatic Models of Mediation, Mandatory Eclectics or a Direct Decision - Chitashvili, Natia; Burduli, Irakli (PRAWO i WIĘŹ, 2024)
The paper conceptually reviews the paradigmatic models of mediation to understand the professional role of a mediator and the scope of ethical obligations. The description of each model presents the corresponding action of a mediator and the standard of intervention in the process, and examines their effectiveness in achieving the goals of mediation. In this regard, the paper examines the content of a mediator's ethical obligations and potential dilemmas in different mediation models that may be associated with a mediator's direct and uniform choice of a particular mediation model. The paper emphasises the importance of a mediator's competence for the proper functioning of a process and, at the same time, analyses the need for a strict demarcation from the professional role of an attorney, which is essential for the ethical execution of a mediator’s role.